2018
DOI: 10.1002/pssb.201800011
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Prediction of Mechanical and Electronic Properties of Ultrahigh Temperature High‐Entropy Ceramics (Hf0.2Zr0.2Ta0.2M0.2Ti0.2)B2 (M = Nb, Mo, Cr)

Abstract: High-entropy metal diborides (Hf 0.2 Zr 0.2 Ta 0.2 M 0.2 Ti 0.2 )B 2 (M ¼ Nb, Mo, Cr) are a new class of ultrahigh temperature ceramics. The novel structural, mechanical, and electronic properties of (Hf 0.2 Zr 0.2 Ta 0.2 M 0.2 Ti 0.2 )B 2 (M ¼ Nb, Mo, Cr) are studied within density functional theory, with the compositional disorder being treated using the special quasi-random structures technique. The elastic stiffness constants C ij , as well as bulk, shear and Young's modulus of (Hf 0.2 Zr 0.2 Ta 0.2 M 0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 57 publications
3
28
1
Order By: Relevance
“… and a = 0.3103(3) nm and c = 0.3367(9) nm from Ref. ), but lower than values of a = 0.3116 nm and c = 0.3391 nm predicted in a previous computational study . The larger lattice parameters measured in the present study indicated that more of the larger transition metal species (eg, a = 0.317 nm and c = 0.354 nm for ZrB 2 ) were incorporated into the lattice of the HEB powders.…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“… and a = 0.3103(3) nm and c = 0.3367(9) nm from Ref. ), but lower than values of a = 0.3116 nm and c = 0.3391 nm predicted in a previous computational study . The larger lattice parameters measured in the present study indicated that more of the larger transition metal species (eg, a = 0.317 nm and c = 0.354 nm for ZrB 2 ) were incorporated into the lattice of the HEB powders.…”
Section: Resultscontrasting
confidence: 66%
“…12 ), but lower than values of a = 0.3116 nm and c = 0.3391 nm predicted in a previous computational study. 13 The larger lattice parameters measured in the present study indicated that more of the larger transition metal species (eg, a = 0.317 nm and c = 0.354 nm for ZrB 2 ) were incorporated into the lattice of the HEB powders. These results indicated that the two step synthesis process used in the present study was better at producing uniform solid solutions than other processes.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Although the initial work on high-entropy borides resulted in relatively low densities (~ 92%) due to significant oxide contamination from high-entropy ball milling, several subsequent studies quickly improved powder synthesis and fabrication methods that enhanced relative densities and properties [46,47,[49][50][51][52][53][54][55][56]. In 2018 and 2019, several groups [21,22,[57][58][59][60][61][62][63][64][65][66] also independently reported the fabrications of high-entropy carbides as another subclass of high-entropy UHTCs.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…Additionally, modeling has revealed the importance of size and interatomic force constant disorder resulting in thermally-insulative HECs [78,[108][109][110]. Various other modeling studies have been conducted [60,[111][112][113][114][115]. A complete review and critical assessment of the modeling of HECs is beyond the scope of this perspective article.…”
Section: Modelingmentioning
confidence: 99%